1998
DOI: 10.1002/(sici)1096-9861(19980720)397:1<41::aid-cne4>3.3.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Striatin, a newly identified calmodulin‐binding protein in the rat brain: An in situ hybridization and immunocytochemical study

Abstract: Striatin, a 110-kDa protein, is the first member of the tryptophane-aspartate repeat protein family known to bind calmodulin in the presence of Ca2+. We examined the distribution of striatin and its mRNA in the rat central nervous system (CNS) by using immunocytochemistry and in situ hybridization, respectively. Striatin immunostaining and mRNA labeling patterns are generally concordant. Regions showing the most intense staining are the dorsal striatum, nucleus accumbens (anterior and shell parts), olfactory t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
7
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
3
7
0
1
Order By: Relevance
“…Striatin is expressed in the CNS, where it is prominent in structures related to locomotor function (Castets et al 1996;Salin et al 1998). The present study demonstrates that striatin has a more widespread distribution than previously shown, and is also present in sensory neurones.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Striatin is expressed in the CNS, where it is prominent in structures related to locomotor function (Castets et al 1996;Salin et al 1998). The present study demonstrates that striatin has a more widespread distribution than previously shown, and is also present in sensory neurones.…”
Section: Discussionsupporting
confidence: 61%
“…The striatin family includes three intracellular proteins, principally expressed in neurones of the mammalian central nervous system (CNS): striatin (Castets et al 1996;Salin et al 1998), zinedin and SG2NA (Castets et al 2000). The three proteins share numerous identical protein-protein interaction domains that are, from the Nto the C-termini, a caveolin-binding domain (Gaillard et al 2001), a putative coiled-coil structure, a Ca 2+ -calmodulin-binding domain ) and a large WDrepeat domain.…”
Section: Introductionmentioning
confidence: 99%
“…The pGEX‐caveolin‐1 full length plasmid was a gift of Dr. Andrew Quest (University of Chile, Santiago, Chile) [16]. The pGEX‐P‐striatin 1–427 plasmid was constructed by inserting two complementary oligonucleotides (5′‐GATCTCTGGAAGTGCTCTTCCAGGGTCCGC‐3′ and 5′‐GATCGCGGACCCTGGAAGAGCACTTCCAGA‐3′) encoding the PreScission Protease site (Amersham Pharmacia Biotech, Piscataway, NJ, USA) into the Bam H‐1 site of the pGEX‐striatin 1–427 plasmid [5]. The sequence of the resulting plasmid was verified (ESGS, Evry, France).…”
Section: Methodsmentioning
confidence: 99%
“…(4)(5)(6) The striatin family proteins are highly expressed in the central and peripheral nervous systems, and partial knockdown of striatin in the rat brain and rat neuron cultures induces a decrease in nocturnal locomotor activity and defects in dendritic growth, respectively. (7)(8)(9) The striatin family is also expressed in additional tissues and cell lines, and these proteins are reported to regulate the localization of the tight junction protein ZO1 and the estrogen-induced activation of endothelial NO synthase. (10,11) Striatin family proteins are also known to form a complex with protein phosphatases and protein kinases.…”
mentioning
confidence: 99%